2018
DOI: 10.1103/physrevfluids.3.054607
|View full text |Cite
|
Sign up to set email alerts
|

Wake meandering of a model wind turbine operating in two different regimes

Abstract: The flows behind a model wind turbine under two different turbine operating regimes (Region 2 for turbine operating at optimal condition with the maximum power coefficient and 1.4 degrees of pitch angle, and Region 3 for turbine operating at sub-optimal condition with a lower power coefficient and 7 degrees of pitch angle) are investigated using wind tunnel experiments and large-eddy simulations (LES). Measurements from the model wind turbine experiment reveal that the power coefficient and turbine wake are af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 77 publications
(107 reference statements)
4
38
0
Order By: Relevance
“…According to Magnusson (1999), this near-wake flow pattern is associated with a reduction in lift, and correspondingly axial induction, at the blade roots. This accelerated flow region has been observed in wind tunnel studies where the model blade geometries cause a similar reduction in lift at the roots (Hancock & Pascheke 2014, Foti et al 2018, and in LES studies where the turbine geometry accurately represents a fieldscale turbine (Schulz et al 2017). Gallacher & More (2014) observed this phenomenon in the average sense using nacelle-mounted lidar on an offshore wind turbine.…”
Section: Mean Wake Statisticssupporting
confidence: 54%
“…According to Magnusson (1999), this near-wake flow pattern is associated with a reduction in lift, and correspondingly axial induction, at the blade roots. This accelerated flow region has been observed in wind tunnel studies where the model blade geometries cause a similar reduction in lift at the roots (Hancock & Pascheke 2014, Foti et al 2018, and in LES studies where the turbine geometry accurately represents a fieldscale turbine (Schulz et al 2017). Gallacher & More (2014) observed this phenomenon in the average sense using nacelle-mounted lidar on an offshore wind turbine.…”
Section: Mean Wake Statisticssupporting
confidence: 54%
“…An actuator surface model for the nacelle was then developed in [3], which can predict the interaction of the nacelle-induced hub vortex with the tip shear layer on relatively coarse grids, as shown in Figure 5c. The effect of nacelle on wake meandering for different operational regimes was also examined [66]. It was found that the amplitudes of wake meanders are underpredicted for the simulation without a nacelle model.…”
Section: Figurementioning
confidence: 99%
“…In [71], Heisel et al studied the spectral characteristics of wake meandering using both wind tunnel and field-scale measurements. It is noted that, in this review, we refer to turbines such as the EOLOS turbine of 96 m rotor diameter as utility scale, the SWiFT turbine of 27 m rotor diameter and above as field scale, and turbines employed in wind tunnels (e.g., the G-1 wind turbine model of rotor diameter 1.1 m [66] and the miniature model turbine of rotor diameter 0.13 m [64]) as laboratory scale. A deficit of the energy of the large-scale eddies (as shown in Figure 7a,b for the field-scale measurements) is observed in both measurements, which is caused by the transfer of energy from the large-scale eddies to the small scales in the turbine wake, which was also observed in numerical simulations, as shown in Figure 6.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations